Comparison of the fungi Pestalotiopsis funerea (Desm.) Steyaert and Truncatella hartigii (Tubeuf) Steyaert isolated from some species of the genus Pinus L. in morphological characteristics of conidia and appendages - H. Ivanová (Journal of Forest Science, 2016)
The similarity of and differences between the fungi Pestalotiopsis funerea (Desmazières) Steyaert and Truncatella hartigii (Tubeuf) Steyaert that damage the needles of the host plants Pinus ponderosa Peter & Charles Lawson, Pinus coulteri D. Don and Pinus nigra Arnold planted in Mlyňany Arborétum, were evaluated with emphasis on comparison of the morphology of their conidia and appendages. Conidia of P. funerea were fusiform to ellipsoid, straight to slightly curved, 4-septate with 3 (4-6) apical sometimes branched appendages. The basal cell was short, hyaline, obtuse and thin-walled with basal, hyaline, filiform, straight, unbranched and single appendage. Conidia of T. hartigii were fusiform, 3-septate, without basal appendages. 2-3 apical appendages arising from the apical cell were attenuated, flexuous, sometimes dichotomously branched. The highest occurrence of the fungi P. funerea and T. hartigii indicates the influence of biotic stresses on properties of these pine trees.